Human-Centered Design Science Research Evaluation for Gamified Augmented Reality - Vasilevski, Nikolche; Birt, James (Frontiers in Virtual Reality, 2021)
As augmented reality (AR) and gamification design artifacts for education proliferate in the mobile and wearable device market, multiple frameworks have been developed to implement AR and gamification. However, there is no explicit guidance on designing and conducting a human-centred evaluation activity beyond suggesting possible methods that could be used for evaluation. This paper proposes a human-centered design evaluation pattern for gamified augmented reality using Design Science Research Methodology (DSRM) to support educators and developers in constructing immersive AR games for education. Specifically, we present an evaluation pattern for a location-based educational indigenous experience that can be used as a case study to support the design of augmented (or mixed) reality interfaces, gamification implementations, and location-based services. The results of the evaluation of three design iterations obtained in the development cycle of a gamified micro-location AR mobile solution showed that the evaluation process could be reused, evolved, and its complexity reduced. Furthermore, the pattern is compatible with formative and summative evaluation and the technical or human-oriented types of evaluation. With this paper, our goal is to provide a step towards a structured use of design patterns for the evaluation of gamified AR apps and at the same time informing the artifact evaluation as well as development in the fields of gamification and immersive technology in general.